Effective Hourly Rates of Contingency-Fee Lawyers: Competing Data and Non-Competitive Fees - Lester Brickman (Washington University Law Quarterly, 2003)
Over the past forty years, the scope of liability assessed under the aegis of the tort system has greatly expanded. This expansion has not been a function of increasing rates of injury in society. Rather, it has been driven by the substantially increasing yield from contingent fees realized by plaintiff lawyers. Since 1960, the effective hourly rates of tort lawyers have increased 1000% to 1400% (in inflation-adjusted dollars) while the overall risk of nonrecovery has remained essentially constant—though it has decreased materially for such high-end tort categories as products liability and medical malpractice. Most cited as authoritative is a set of data indicating that the yields of contingent-fee claiming approximate the returns realized by hourly rate lawyers. These data—central to contentions that tort reform efforts are not only unnecessary but also counterproductive in that they would deny claimants access to justice—are unreliable and invalid. More reliable data, which I present, demonstrate that the yields from contingency-fee practice have become inordinately high; indeed, they have increased enormously in recent decades, often amounting today to thousands of dollars an hour. In theory, these yields implicate ethical rules purporting to limit fees to “reasonable” amounts. In fact, “reasonable fee” rules are largely a shibboleth. The real role of ethical rules is to inhibit price competition so that tort lawyers can continue to extract substantial rents.
Keywords: Contingent fees; Tort reform; Social science research; Lawyers' fees